Implementation of Production Sharing Agreements for Agricultural Land in Indonesia - Hutapea, Maria; Krismantoro, D.; Joe, Christian (Westscience Press, 2025)
Production Sharing Agreement is an agreement made between the owner and the cultivator of paddy land. The cultivator is asked by the owner to work or cultivate the owner's paddy field whose object is not the paddy field but something attached to the paddy field such as rice plants. The problem in this study is how the implementation of profit-sharing agreements for paddy fields in Indonesia. The research method used is normative juridical. The data source used is secondary data. The method of data collection is done by means of literature study. Data processing is done by means of descriptive analytics. Based on Law Number 2 of 1960 concerning Production Sharing Agreements that in Indonesia it is required that the production sharing agreement must be made by the owner witnessed by two witnesses, each from the landowner and cultivator. In reality, production sharing agreements made by the Indonesian people are still based on customary law so that the agreement is only done orally, not made before the village head and not witnessed by witnesses.